Growth rate analysis of male and female Arctic charr (Salvelinus Alpinus) in Þríhyrningsvatn - Katrín Kjartansdóttir 1998- (2021)
Vaxtarhraði er eitt af helstu einkennum fiskstofna og ýmsir þættir hafa áhrif á hann. Vaxtarhraði bleikju (Salvelinus alpinus) í Þríhyrningsvatni var rannsakaður og tilgátan um að hængar hefðu meiri vaxtarhraða en hrygnur prófuð. Fiskarnir voru veiddir í net á tveimur mismunandi stöðum í vatninu, lengd og þyngd voru mæld og kvarnir notaðar til að ákvarða aldur. Ekki fannst marktækur munur á vaxtarhraða kynjanna (ANOVA, 56 df, p<0.05). Marktækur munur fannst hinsvegar á meðallengd kynjanna (t-test, 61 df, p<0.05) og þyngd þeirra (t-test, F-test, 61 df, p<0.05). Growth rate is influenced by many factors and is one of the defining characteristics for any fish population. In this research growth rate of Arctic charr (Salvelinus alpinus) in Þríhyrningsvatn was inspected and the hypothesis of males having a higher growth rate than females tested. The fish were caught with gill nets in two different areas of the lake, length and weight measured and otoliths used to determine age. No significance difference between growth rate of the sexes was detected (ANOVA, 56 df, P>0.05). However, the males were found to have significantly higher values of mean length (t-test, 61 df, P<0.05) and there was significant difference in weight between the sexes (t-test, F-test, 61 df, P<0.05).